2016
DOI: 10.1021/acssynbio.6b00017
|View full text |Cite
|
Sign up to set email alerts
|

GreA and GreB Enhance Expression of Escherichia coli RNA Polymerase Promoters in a Reconstituted Transcription–Translation System

Abstract: Cell-free environments are becoming viable alternatives for implementing biological networks in synthetic biology. The reconstituted cell-free expression system (PURE) allows characterization of genetic networks under defined conditions but its applicability to native bacterial promoters and endogenous genetic networks is limited due to the poor transcription rate of Escherichia coli RNA polymerase in this minimal system. We found that addition of transcription elongation factors GreA and GreB to the PURE syst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Recently, studies in Salmonella enterica serovar Typhimurium demonstrated that GreA-mediated rescue of backtracked paused complexes during transcription is crucial in promoting hilD expression through its 3 -UTR (Gaviria-Cantin et al, 2017). In addition, GreA enhanced expression of several E. coli RNAP promoters in vitro (Erie et al, 1993;Feng et al, 1994;Hsu et al, 1995;Maddalena et al, 2016). Given that GreA has a multitude of effects on transcription, initiation, and elongation (Stepanova et al, 2007;Vinella et al, 2012), this could explain our failure to identify the binding motif of GreA.…”
Section: Transcription Regulation By the M Smegmatis Transcription Ementioning
confidence: 98%
“…Recently, studies in Salmonella enterica serovar Typhimurium demonstrated that GreA-mediated rescue of backtracked paused complexes during transcription is crucial in promoting hilD expression through its 3 -UTR (Gaviria-Cantin et al, 2017). In addition, GreA enhanced expression of several E. coli RNAP promoters in vitro (Erie et al, 1993;Feng et al, 1994;Hsu et al, 1995;Maddalena et al, 2016). Given that GreA has a multitude of effects on transcription, initiation, and elongation (Stepanova et al, 2007;Vinella et al, 2012), this could explain our failure to identify the binding motif of GreA.…”
Section: Transcription Regulation By the M Smegmatis Transcription Ementioning
confidence: 98%
“…(C) Optimization of the system can be carried out by adjusting both protein and energy solution components. Potential system modifications are shown: (D) supplementation with E. coli RNAP allows for more complex transcription regulation (Maddalena et al, 2016); (E) addition of chaperones aids protein folding (Niwa et al, 2012); (F) vesicles enable membrane protein folding and assembly (Kuruma and Ueda, 2015;Niwa et al, 2015a;Jacobs et al, 2019); and (G) oxidizing conditions allow for disulfide bond formation (Shimizu et al, 2005). (Tuckey et al, 2014), and Magic PURE system (Creative Biolabs).…”
Section: Recombinant Systemsmentioning
confidence: 99%
“…This improvement lowers the price of the energy source and simplifies the energy regeneration process (Wang et al, 2019). While the original PURE system only contains T7 RNA polymerase, with its limited capability for transcriptional regulation, E. coli σ -factor based transcription has been successfully demonstrated, albeit with low efficiency with certain promoters, which can be enhanced by adding purified E. coli polymerase alone or in combination with transcription elongation factors (Maddalena et al, 2016) (Figure 2D).…”
Section: Recombinant Systemsmentioning
confidence: 99%
“…16 A likely explanation for this discrepancy is the decoupling of RNA and protein synthesis when using T7 RNA polymerase and E. coli ribosomes. 1,16,25 Perhaps substituting T7 RNA polymerase with E. coli RNA polymerase, as in ePURE, 34 would allow for proper coupling and thus the ability to predictably control protein output through the activity of the transcriptional promoter.…”
Section: A Better Understanding Of the Influence Of Rna Folding On Trmentioning
confidence: 99%